Răspuns :
a) a = - 5; b + c = 11
3 a + b√2 + c√2 = 11√2 - 15
= 3 × ( - 5 ) + √2 × ( b + c ) =
= - 15 + √2 × 11 =
= 11√2 - 15
________________________
b) a + b = 7; b + c = - 3
2 a + 5 b + 3 c = 5
= 2 a + 2 b + 3 b + 3 c =
= 2 × ( a + b ) + 3 × ( b + c ) =
= 2 × 7 + 3 × ( - 3 ) =
= 14 - 9 =
= 5
__________________
c)
3 a + 2 b - c = 10
5 a + 7 b + 6 c = 2
__________________ adun relatiile
8 a + 9 b + 5 c = 12
___________________________________________
d)
4 m - 3 n - 5 = 0
( 11 - 8 m + 6 n )¹⁰⁰= 1
= [1 - 2 × ( 4 m - 3 n - 5 ) ]¹⁰⁰ =
= ( 1 - 2 × 0 )¹⁰⁰ =
= 1¹⁰⁰ =
= 1